In-situ synthesized halogen modified bismuth nano electro-catalysis electrode as well as preparation method and application thereof
By halogenating the surface of bismuth-based nanomaterials, an electrocatalytic electrode of bismuth nanocatalytic material with halogen modification is formed, which solves the problem of insufficient application of bismuth-based nanomaterials in the prior art, and achieves efficient CO2 reduction to formic acid catalytic properties.
Patent Information
- Application Number
- CN202411980106.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-31
AI Technical Summary
There is a lack of research on the surface halogenation of bismuth-based nanomaterials and their application in electrochemical CO2 reduction in the prior art, which has affected the improvement of catalytic performance.
The alkaline bismuth nitrate nanoflowers are surface halogenated by water bath to synthesize the precursor, and the precursor is reduced in situ under electrocatalytic CO2 reduction conditions to form an electrocatalytic electrode with halogen-modified bismuth nanocatalytic material.
The performance of high selective electrochemical reduction of bismuth nanocatalytic materials to formic acid is achieved, and the preparation method is simple, the reaction is gentle, and it has good application prospects.
Smart Images

Figure CN119433589A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrocatalytic reduction of carbon dioxide, and specifically relates to an in-situ synthesized halogen-modified bismuth nano-electrocatalytic electrode and a preparation method and application thereof. Background Art
[0002] Since the Industrial Revolution, the development of fossil fuels has led to an increase in the concentration of CO2 in the earth's atmosphere year by year. This has caused a series of environmental problems, such as global warming, rising sea levels, and glacier melting. In order to reduce the concentration of CO2 or convert CO2 into economically valuable chemicals, various technologies have been proposed. Among them, electrochemical CO2 reduction technology (CO2RR) can convert CO2 into valuable liquid chemicals or fuels, and is an effective technology for achieving carbon neutrality and carbon peak. In the past decade, different catalysts have been developed to convert CO2 into various gaseous or liquid products such as carbon monoxide, formic acid, ethylene, ethanol, n-propanol, etc. through CO2RR. Among the liquid products, formic acid has attracted much attention due to its economic feasibility and high hydrogen capacity.
[0003] In recent years, transition metal-based electrocatalysts, such as tin (Sn), indium (In), bismuth (Bi) and lead (Pb), have been widely studied as typical catalysts for the electrocatalytic reduction of CO2 to formic acid because they have strong adsorption effects on key intermediates in the formation of formic acid and inhibit the competitive hydrogen evolution reaction. Among them, bismuth-based nanocatalysts have attracted much attention from researchers due to their high selectivity for the electrochemical reduction of CO2 to formic acid in a wide potential window, as well as their relatively abundant reserves, non-toxicity and low cost. In order to continuously improve the performance of bismuth-based catalysts, researchers have adopted a variety of regulatory strategies to regulate the morphology of bismuth nanomaterials and introduce defects so that bismuth-based nanomaterials have abundant active sites, such as edges, defects, grain boundaries and high-index facets.
[0004] The study found that halogen ions can be anchored on Bi atoms by replacing the surface hydroxyl groups, achieving surface halogenation of bismuth basic nitrate, which promotes local charge separation on the one hand, and activates the hydroxyl groups on the other hand, which is beneficial to the adsorption of CO2 molecules and protons and promotes the photocatalytic CO2 conversion process. However, there are no reports on the surface halogenation of bismuth-based nanomaterials and their application in electrochemical CO2 reduction. Therefore, it is necessary to study the effect of surface halogenation of halogen anions on the electrochemical CO2 reduction performance. Summary of the invention
[0005] The purpose of the present invention is to provide an in-situ synthesized halogen-modified bismuth nano-electrocatalytic electrode and its preparation method and application, which comprises performing surface halogenation on basic bismuth nitrate nanoflowers in a water bath to synthesize a precursor, and then in-situ reducing the precursor under electrocatalytic CO2 reduction conditions to form an electrocatalytic electrode having a halogen-modified bismuth nano-catalytic material, and the electrocatalytic electrode exhibits good performance in electrocatalytic reduction of CO2 to formic acid, and has good application prospects.
[0006] To achieve the above object, the present invention adopts the following technical solution: An in-situ synthesized halogen-modified bismuth nanoelectrocatalytic electrode, the synthesis method of which comprises the following steps: 1) Dissolve 0.01-200 mmol Bi(NO3)3∙5H2O and 0.01-200 mmol cetyltrimethylammonium bromide (CTAB) in 6-600 mL deionized water, and stir vigorously for 30 minutes to obtain solution A; dissolve 0.005-0.05 mol alkali metal hydroxide in 4-400 mL ethanol, and stir vigorously for 30 minutes to obtain solution B; quickly pour solution B into solution A, and stir vigorously for 10-1000 minutes to obtain solution C; transfer solution C to a 50-90°C water bath, stir vigorously for 1-10 hours, and after cooling to room temperature, collect the product by centrifugation, wash it alternately with ethanol and deionized water twice each, and then dry it at 40-60°C overnight to obtain basic bismuth nitrate powder; 2) dissolving 0.01-200 mmol of metal halide in 5-500 mL of deionized water, stirring for 3-300 minutes to obtain solution D; adding 1-100 mg of the basic bismuth nitrate powder obtained in step 1) to solution D, stirring for 1-24 hours at room temperature in the dark, then repeatedly washing with deionized water, and finally drying at 40-60° C. for 15 hours to obtain a precursor powder BON-X (X is a halogen); 3) The precursor powder BON-X obtained in step 3) is uniformly dispersed in an organic solvent, and subjected to ultrasonic treatment in an ice-water bath for 0.5-20 hours to obtain an electrode slurry; the obtained electrode slurry is drop-coated in small amounts and multiple times on the center of the side of the carbon paper loaded with the microporous carbon layer, and after drying, it is used as a working electrode, and electrolysis is performed under ECR conditions to in situ synthesize an electrocatalytic electrode with a halogen-modified bismuth nanocatalytic material.
[0007] Furthermore, the alkali metal hydroxide in step 1) includes Bi6O6(OH3)(NO3)3·1.5H2O or Bi6O5(OH3)(NO3)·3H2O.
[0008] Furthermore, the metal halide in step 2) includes any one of sodium fluoride, sodium iodide, sodium bromide, potassium fluoride, potassium iodide and potassium bromide.
[0009] Furthermore, the organic solvent in step 3) is an ethanol solution containing 5 vol% Nafion.
[0010] Furthermore, in step 3), the concentration of the electrode slurry is 1-50 mg / ml.
[0011] Furthermore, in step 3), the amount of electrode slurry applied on the carbon paper is 100-1000 μL / cm 2 .
[0012] Furthermore, in step 3), during electrolysis, a 5-500 mL H-type electrolytic cell is selected, a 0.5 M KHCO3 solution is used as the electrolyte solution (and the electrolyte in the cathode cell should be in a CO2-saturated state), a platinum electrode is used as the counter electrode, and a saturated Ag / AgCl electrode is used as the reference electrode to construct a three-electrode system, and a constant current treatment is performed at 5-150 mA for 5-60 min.
[0013] The halogen-modified bismuth nano-electrocatalytic electrode exhibits good performance in electrocatalytic reduction of CO2 to formic acid, and can be applied to electrocatalytic reduction of carbon dioxide to formic acid.
[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses alkali metal hydroxide as a precipitant and CTAB as a directing agent and a surfactant to prepare basic bismuth nitrate by a simple hydrolysis method, and then grafts halogen atoms on the surface of the basic bismuth nitrate by water bath treatment to obtain a BON-X precursor, and then in situ electro-reduction is performed under ECR conditions to synthesize an electrocatalytic electrode with a halogen-modified bismuth nanocatalytic material. The preparation method is simple, the reaction is relatively mild, the process is convenient, and the time is short.
[0015] (2) The halogen-modified bismuth nanocatalytic material prepared by the present invention exhibits good catalytic activity for the electrocatalytic reduction of CO2 to formic acid and high single selectivity, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The XRD spectra of the precursor powders prepared in Examples 1-4 are shown in FIG.
[0017] Figure 2 Comparison of linear sweep voltammetry (LSV) curves of the electrocatalytic electrodes prepared in Examples 1-4 in a CO2-saturated 0.5M KHCO3 electrolyte.
[0018] Figure 3 The Faraday efficiency (FE) of the product formic acid produced by the electrocatalytic electrode prepared in Examples 1-4 at different potentials for 1 hour HCOOH ) comparison chart. DETAILED DESCRIPTION
[0019] An in-situ synthesized halogen-modified bismuth nanoelectrocatalytic electrode, the synthesis method of which comprises the following steps: 1) Dissolve 0.01-200 mmol Bi(NO3)3∙5H2O and 0.01-200 mmol cetyltrimethylammonium bromide (CTAB) in 6-600 mL deionized water, and stir vigorously for 30 minutes to obtain solution A; dissolve 0.005-0.05 mol alkali metal hydroxide in 4-400 mL ethanol, and stir vigorously for 30 minutes to obtain solution B; quickly pour solution B into solution A, and stir vigorously for 10-1000 minutes to obtain solution C; transfer solution C to a 50-90°C water bath, stir vigorously for 1-10 hours, and after cooling to room temperature, collect the product by centrifugation, wash it alternately with ethanol and deionized water twice each, and then dry it at 40-60°C overnight to obtain basic bismuth nitrate powder; 2) dissolving 0.01-200 mmol of metal halide in 5-500 mL of deionized water, stirring for 3-300 minutes to obtain solution D; adding 1-100 mg of the basic bismuth nitrate powder obtained in step 1) to solution D, stirring for 1-24 hours at room temperature in the dark, then repeatedly washing with deionized water, and finally drying at 40-60° C. for 15 hours to obtain a precursor powder BON-X (X is a halogen); 3) The precursor powder BON-X obtained in step 3) is uniformly dispersed in an ethanol solution containing 5 vol% Nafion, and ultrasonicated in an ice-water bath for 0.5-20 hours to obtain an electrode slurry with a concentration of 1-50 mg / ml; the obtained electrode slurry is heated at 100-1000 μL / cm 2 The amount of bismuth nanoparticles was drop-coated on the center of the side of the carbon paper loaded with the microporous carbon layer in small amounts several times. After drying, it was used as the working electrode, and a platinum electrode was used as the counter electrode. A saturated Ag / AgCl electrode was used as the reference electrode to construct a three-electrode system. In a 5-500 mL H-type electrolytic cell, a 0.5 M KHCO3 solution was used as the electrolyte solution (the electrolyte in the cathode cell should be in a CO2-saturated state), and constant current electrolysis was performed at 5-150 mA for 5-60 min to in situ synthesize an electrocatalytic electrode with halogen-modified bismuth nanocatalytic material.
[0020] Wherein, the alkali metal hydroxide in step 1) includes Bi6O6(OH3)(NO3)3·1.5H2O or Bi6O5(OH3)(NO3)·3H2O.
[0021] The metal halide in step 2) includes any one of sodium fluoride, sodium iodide, sodium bromide, potassium fluoride, potassium iodide and potassium bromide.
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1 The preparation of BON electrocatalytic electrode includes the following steps: (1) 4 mmoL Bi(NO3)3∙5H2O and 2 mmoL CTAB were dissolved in 200 mL deionized water and stirred vigorously for 30 minutes to obtain solution A; 0.1 mol urea was dissolved in 100 mL ethanol and stirred vigorously for 30 minutes to obtain solution B; solution B was quickly poured into solution A and stirred vigorously for 30 minutes to obtain solution C; solution C was transferred to a 75°C water bath and stirred vigorously for 10 hours. After cooling to room temperature, the product was collected by centrifugation, washed alternately with ethanol and deionized water twice each, and dried at 45°C overnight to obtain basic bismuth nitrate powder.
[0024] (2) 20 mg of the obtained bismuth basic nitrate powder was uniformly dispersed in 4 mL of ethanol solution containing 5 vol% Nafion, and ultrasonicated in an ice-water bath for 4 hours to obtain an electrode slurry; the obtained electrode slurry was dripped on the center of the side of the carbon paper loaded with the microporous carbon layer in small amounts and multiple times using a pipette, and the dripping amount was 100 μL / cm 2 After drying, it was prepared into a working electrode, and a three-electrode system was constructed with a platinum sheet electrode as a counter electrode and a saturated Ag / AgCl electrode as a reference electrode. In a 100 mL H-type electrolytic cell, 0.5 M KHCO3 solution was used as the electrolyte solution (the electrolyte in the cathode cell should be in a CO2-saturated state), and constant current electrolysis was performed at 150 mA for 1 h to in situ synthesize an electrocatalytic electrode with BON catalytic material.
[0025] Example 2 The preparation of the BON-Cl electrocatalytic electrode includes the following steps: (1) 4 mmoL Bi(NO3)3∙5H2O and 2 mmoL CTAB were dissolved in 200 mL deionized water and stirred vigorously for 30 minutes to obtain solution A; 0.1 mol urea was dissolved in 100 mL ethanol and stirred vigorously for 30 minutes to obtain solution B; solution B was quickly poured into solution A and stirred vigorously for 30 minutes to obtain solution C; solution C was transferred to a 75°C water bath and stirred vigorously for 10 hours. After cooling to room temperature, the product was collected by centrifugation, washed alternately with ethanol and deionized water twice each, and dried at 45°C overnight to obtain basic bismuth nitrate powder.
[0026] (2) 8 mmol NaCl was dissolved in 100 mL deionized water and stirred for 30 minutes to obtain solution D; 100 mg of the basic bismuth nitrate powder prepared in step (1) was added to solution D, stirred in the dark at room temperature for 24 hours, then repeatedly washed with deionized water, and finally dried at 45°C for 15 hours to obtain BON-Cl precursor powder.
[0027] (3) Disperse 20 mg of the obtained BON-Cl precursor powder evenly into 4 mL of ethanol solution containing 5 vol% Nafion, and ultrasonicate in an ice-water bath for 4 h to obtain an electrode slurry. Use a pipette to drop the obtained electrode slurry in small amounts and multiple times on the center of the side of the carbon paper loaded with the microporous carbon layer. The drop amount is 100 μL / cm 2 After drying, it was prepared into a working electrode, and a three-electrode system was constructed with a platinum sheet electrode as a counter electrode and a saturated Ag / AgCl electrode as a reference electrode. In a 100 mL H-type electrolytic cell, 0.5 M KHCO3 solution was used as the electrolyte solution (the electrolyte in the cathode cell should be in a CO2-saturated state), and constant current electrolysis was performed at 150 mA for 1 h to in situ synthesize an electrocatalytic electrode with BON-Cl catalytic material.
[0028] Example 3 The preparation of BON-I electrocatalytic electrode includes the following steps: (1) 4 mmoL Bi(NO3)3∙5H2O and 2 mmoL CTAB were dissolved in 200 mL deionized water and stirred vigorously for 30 minutes to obtain solution A; 0.1 mol urea was dissolved in 100 mL ethanol and stirred vigorously for 30 minutes to obtain solution B; solution B was quickly poured into solution A and stirred vigorously for 30 minutes to obtain solution C; solution C was transferred to an 85°C water bath and stirred vigorously for 10 hours. After cooling to room temperature, the product was collected by centrifugation, washed alternately with ethanol and deionized water twice each, and dried at 45°C overnight to obtain basic bismuth nitrate powder.
[0029] (2) 8 mmol KI was dissolved in 100 mL deionized water and stirred for 30 minutes to obtain solution D. 100 mg of the basic bismuth nitrate powder prepared in step (1) was added to solution D, stirred in the dark at room temperature for 24 hours, then repeatedly washed with deionized water, and finally dried at 45°C for 15 hours to obtain BON-I precursor powder.
[0030] (3) Disperse 20 mg of the obtained BON-I precursor powder evenly into 4 mL of ethanol solution containing 5 vol% Nafion, and ultrasonicate in an ice-water bath for 4 h to obtain an electrode slurry. Use a pipette to drop the obtained electrode slurry in small amounts and multiple times on the center of the side of the carbon paper loaded with the microporous carbon layer. The drop amount is 100 μL / cm 2 After drying, the working electrode was prepared, and a three-electrode system was constructed with a platinum sheet electrode as the counter electrode and a saturated Ag / AgCl electrode as the reference electrode. In a 100 mL H-type electrolytic cell, a 0.5 M KHCO3 solution was used as the electrolyte solution (the electrolyte in the cathode cell should be in a CO2-saturated state), and constant current electrolysis was performed at 150 mA for 1 h to in situ synthesize an electrocatalytic electrode with BON-I catalytic material.
[0031] Example 4 The preparation of BON-F electrocatalytic electrode includes the following steps: (1) 4 mmoL Bi(NO3)3∙5H2O and 2 mmoL CTAB were dissolved in 200 mL deionized water and stirred vigorously for 30 minutes to obtain solution A; 0.1 mol urea was dissolved in 100 mL ethanol and stirred vigorously for 30 minutes to obtain solution B; solution B was quickly poured into solution A and stirred vigorously for 30 minutes to obtain solution C; solution C was transferred to a 75°C water bath and stirred vigorously for 5 hours. After cooling to room temperature, the product was collected by centrifugation, washed alternately with ethanol and deionized water twice each, and dried at 45°C overnight to obtain basic bismuth nitrate powder.
[0032] (2) 8 mmol NaF was dissolved in 100 mL deionized water and stirred for 30 minutes to obtain solution D; 100 mg of the basic bismuth nitrate powder prepared in step (1) was added to solution D, stirred in the dark at room temperature for 24 hours, then repeatedly washed with deionized water, and finally dried at 45°C for 15 hours to obtain BON-F precursor powder.
[0033] (3) Disperse 20 mg of the obtained BON-F precursor powder evenly into 4 mL of ethanol solution containing 5 vol% Nafion, and ultrasonicate in an ice-water bath for 4 hours to obtain an electrode slurry; use a pipette to drop the obtained electrode slurry in small amounts and multiple times on the center of the side of the carbon paper loaded with the microporous carbon layer, with a drop amount of 100 μL / cm 2 After drying, the working electrode was prepared, and a three-electrode system was constructed with a platinum sheet electrode as the counter electrode and a saturated Ag / AgCl electrode as the reference electrode. In a 100 mL H-type electrolytic cell, a 0.5 M KHCO3 solution was used as the electrolyte solution (the electrolyte in the cathode cell should be in a CO2-saturated state), and constant current electrolysis was performed at 150 mA for 1 h to in situ synthesize an electrocatalytic electrode with BON-F catalytic material.
[0034] Figure 1 The XRD spectra of the precursor powders prepared in Examples 1-4. As can be seen from the figure, diffraction peaks attributed to Bi6O6(OH3)(NO3)3·1.5H2O (PDF#53-1038) and Bi6O5(OH3)(NO3)·3H2O (PDF#48-0575) can be observed from the spectra of BON, BON-I, and BON-Cl precursors, and diffraction peaks attributed to BiOCl (PDF#06-0249) can also be seen from the spectrum of the BON-Cl precursor, while the XRD spectrum of the BON-F precursor only contains diffraction peaks attributed to BiOF (PDF#86-1648) and Bi6O6(OH3)(NO3)3·1.5H2O (PDF#53-1038). In summary, it is shown that the sample does not contain other impurities.
[0035] Application Examples An electrochemical workstation was used to carry out electrochemical testing of the catalyst, and nuclear magnetic resonance hydrogen spectrum and gas chromatography were used to detect the electrocatalytic reduction of CO2 products.
[0036] The electrolyte solution used was 0.5M KHCO3 solution, the test temperature was 25℃, the test system was a three-electrode system, the electrolytic cell was an H-type electrolytic cell, the platinum electrode was the counter electrode, and the saturated Ag / AgCl electrode was the reference electrode. All potentials in the test results were adjusted to the potential relative to the reversible hydrogen electrode (vs. RHE). The linear sweep voltammetry (LSV) test scan rate was 3mV / s. Before the test, the working electrode was subjected to cyclic voltammetry scanning for 20 cycles at a scan rate of 50mV / s. After a linear sweep voltammetry (LSV) test, the catalyst was electrolyzed at different potentials in the constant potential mode. The electrolysis time was 1 hour. During the electrolysis process, the gas phase products were collected and detected by chromatography. After the electrolysis, the electrolyte in the cathode cell was collected for nuclear magnetic resonance detection.
[0037] Figure 2 The LSV curve comparison diagram of the electrocatalytic electrodes obtained in Examples 1-4 in a CO2-saturated 0.5 M KHCO3 cathode electrolyte. As can be seen from the figure, within the test potential range, the reduction current density of the BON-Cl electrocatalytic electrode is significantly greater than that of the BON, BON-I, and BON-F electrocatalytic electrodes.
[0038] Figure 3This is a comparison chart of the Faraday efficiency of the electrocatalytic electrode obtained in Example 1-4 for the electrocatalytic reduction of CO2 to generate formic acid (the test potential range is -0.87V vs. RHE~-1.27V vs. RHE). It can be seen from the figure that within the test range, the formic acid Faraday efficiency of the BON-Cl electrocatalytic electrode is stably maintained at more than 90%, and the Faraday efficiency at high potential is significantly better than that of other catalysts, while the Faraday efficiency of the BON, BON-I, and BON-F electrocatalytic electrodes decreases significantly with the increase of potential. This shows that the BON, BON-Cl, BON-I, and BON-F electrocatalytic electrodes all have good performance in electrocatalytic reduction of carbon dioxide to formic acid, among which the catalytic performance of the BON-Cl electrocatalytic electrode is the best.
[0039] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0040] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This narrative method of the specification is only for clarity. Those skilled in the art should regard the specification as a whole. The technical solutions of each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for in-situ synthesis of halogen-modified bismuth nanoelectrocatalytic electrodes, characterized in that: The steps include: 1) Dissolve 0.01-200 mmol Bi(NO3)3∙5H2O and 0.01-200 mmol CTAB in 6-600 mL deionized water, and stir vigorously for 30 minutes to obtain solution A; dissolve 0.005-0.05 mol alkali metal hydroxide in 4-400 mL ethanol, and stir vigorously for 30 minutes to obtain solution B; quickly pour solution B into solution A, and stir vigorously for 10-1000 minutes to obtain solution C; transfer solution C to a 50-90°C water bath, stir vigorously for 1-10 hours, and after cooling to room temperature, collect the product by centrifugation, wash it alternately with ethanol and deionized water twice each, and then dry it at 40-60°C overnight to obtain basic bismuth nitrate powder; 2) dissolving 0.01-200 mmol of metal halide in 5-500 mL of deionized water, stirring for 3-300 minutes to obtain solution D; adding 1-100 mg of the basic bismuth nitrate powder obtained in step 1) to solution D, stirring for 1-24 hours at room temperature in the dark, then repeatedly washing with deionized water, and finally drying at 40-60° C. for 15 hours to obtain a precursor powder; 3) The precursor powder obtained in step 3) is uniformly dispersed in an organic solvent, and subjected to ultrasonic treatment in an ice-water bath for 0.5-20 hours to obtain an electrode slurry; the obtained electrode slurry is drop-coated in small amounts and multiple times on the center of the side of the carbon paper loaded with the microporous carbon layer, and after drying, it is used as a working electrode for electrolysis under ECR conditions to in situ synthesize an electrocatalytic electrode with a halogen-modified bismuth nanocatalytic material.
2. The method for in-situ synthesis of halogen-modified bismuth nano-electrocatalytic electrodes according to claim 1, characterized in that: The alkali metal hydroxide in step 1) includes Bi6O6(OH3)(NO3)3·1.5H2O or Bi6O5(OH3)(NO3)·3H2O.
3. The method for in-situ synthesis of halogen-modified bismuth nano-electrocatalytic electrodes according to claim 1, characterized in that: The metal halide in step 2) includes any one of sodium fluoride, sodium iodide, sodium bromide, potassium fluoride, potassium iodide and potassium bromide.
4. The method for in-situ synthesis of halogen-modified bismuth nano-electrocatalytic electrodes according to claim 1, characterized in that: The organic solvent in step 3) is an ethanol solution containing 5 vol% Nafion.
5. The method for in-situ synthesis of halogen-modified bismuth nano-electrocatalytic electrodes according to claim 1, characterized in that: The concentration of the electrode slurry in step 3) is 1-50 mg / ml; the amount of the electrode slurry applied on the carbon paper is 100-1000 μL / cm 2 .
6. The method for in-situ synthesis of halogen-modified bismuth nano-electrocatalytic electrodes according to claim 1, characterized in that: Step 3) During electrolysis, a 5-500 mL H-type electrolytic cell is selected, 0.5 M KHCO3 solution is used as the electrolyte solution, a platinum electrode is used as the counter electrode, and a saturated Ag / AgCl electrode is used as the reference electrode to construct a three-electrode system, and constant current treatment is performed at 5-150 mA for 5-60 min.
7. A halogen-modified bismuth nanoelectrocatalytic electrode prepared by the method as claimed in claim 1.
8. Use of the halogen-modified bismuth nano-electrocatalytic electrode as claimed in claim 7 in the electrocatalytic reduction of carbon dioxide to formic acid.
Citation Information
Patent Citations
BiOCl nanoring and synthetic method thereof
CN108502926A
Ov-Bi2O3 catalyst as well as preparation method and application thereof
CN115414928A
Fluorine-modified metal bismuth electrocatalyst and preparation method and application thereof
CN118028867A
Preparation method and application of electrocatalyst for producing formic acid through electrocatalysis of carbon dioxide
CN118704035A
Cited By
Proton sponge modified fluorine atom doped metal copper electrode material and preparation method and application thereof
CN120485862A
A proton sponge modified fluorine atom doped copper electrode material and a preparation method and application thereof
CN120485862B